PERAMALAN AKSEPTOR KB BARU PADA KOTA TANJUNGBALAI DENGAN TEKNIK SINGLE EXPONENTIAL SMOOTHING (SES) - MUHAMMAD RIZKY; RURI ASHARI DALIMUNTHE; Sudarmin Sudarmin (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Improving the quality of health services needs to be done continuously. In general, family planning can be explained that family planning is an effort that regulates the number of births in such a way that for the mother and her baby and for the father and his family or the community concerned there will not be a loss as a direct result of the birth. In a narrow sense, family planning in everyday life revolves around preventing conception or preventing fertilization from meeting the sperm cells (spermatozoa) from men and egg cells (ova) from women. Family planning (KB) acceptors (users) have the right to receive services. quality health care and obtain the 7 rights of patients when they come to health facilities. The fulfillment of the right of family planning (KB) acceptors will be able to help improve the achievement of reproductive health services. The delivery of health information related to reproduction can help motivate family planning (KB) acceptors for a healthy lifestyle and in the end can improve health and save the lives of family planning (KB) acceptors themselves and save the lives of their children. To be able to provide optimal services, of course, adequate contraceptives are needed that are in accordance with the number of family planning (KB) acceptors (users). So the number of contraceptives such as birth control pills, KB injections, implants (Norpant), IUD (Spiral), vasectomy, and tubectomy must be proportional to the number of family planning (KB) acceptors. However, the problem that occurs is the difficulty in determining the number of new Family Planning (KB) participants (Family Planning acceptors) (KB). For this reason, forecasting is needed. So the number of facilities must be proportional to the number of family planning (KB) acceptors. However, the problem that occurs is the difficulty in determining the number of new family planning (KB) participants.